Mengenal Ileus Obstruktif dan Upaya Pencegahannya Sejak Dini di SMA Negeri 13 Bandung - Theophylia Melisa Manumara; Hillya Surya Afdillah; Marcela Anggraeni; Rifa Nurul Fajriani; Dita Apriliyanti; Sefya Fica Wulandari; Susilawati Susilawati; Fahmi Adian Nizar; Aiska Haniyya Muhtar; Titin Hanipah; Nadia Fatma (Jurnal Medika: Medika, 2026)
Obstructive ileus is a surgical emergency characterized by an obstruction of intestinal passage—either partial or total—due to a mechanical blockage. The high incidence of obstructive ileus in Indonesia, particularly in West Java, is a serious concern in the healthcare sector because it still carries a relatively high mortality rate. The general public’s limited knowledge, including among adolescents, regarding the signs and symptoms of obstructive ileus often leads to delays in medical treatment. This community service activity aims to improve the knowledge of students at SMAN 13 Bandung regarding obstructive ileus through structured health education. The methods used include presenting material using PowerPoint, distributing leaflets as self-study materials, and evaluating understanding through a post-test in the form of an interactive quiz. The activity was conducted with students selected through purposive sampling. The evaluation results showed an increase in students’ knowledge following the health education intervention. This activity demonstrated that multimodal health education involving visual media, print media, and interactive assessment is effective in improving adolescents’ knowledge of obstructive ileus. Therefore, a continuous health education program in schools is needed as a preventive and promotive effort to improve community health literacy.